2022
DOI: 10.53730/ijhs.v6ns9.12163
|View full text |Cite
|
Sign up to set email alerts
|

correlation between CD200 expression and oxidant-antioxidant status in newly diagnosed B-chronic lymphocytic leukemia patients

Abstract: B cell chronic lymphocytic leukemia (B-CLL) is the highest incidence of lymphoproliferative malignant disease in most adults in the western world. Due to the importance of the pathogenicity and risk factors of this disease, this study was designed to analyze the expression the pattern of CD200 by flow cytometer immunophenotyping (FCI) and the association between this marker and some clinical features and oxidant-antioxidant status in B-chronic lymphocytic leukemia patients. This study was conducted on 60 newly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…OS in B-CLL is concurrently produced by increased ROS production, related mostly to the mitochondrial activity of B-CLL cells, and insufficient antioxidant defences. [32,33]. The decreased antioxidant capacity found in the sera of our B-CLL patients may be related to a consumption of antioxidants and/or to a reduced efficacy of antioxidant defences due to the systemic excess of ROS that is common in cancer [34].Accumulating evidence by two important studies suggested that increased OS and the relative deficiency of the antioxidant defence system are involved in crucial steps of B-CLL development [28,35].…”
Section: Discussionmentioning
confidence: 95%
“…OS in B-CLL is concurrently produced by increased ROS production, related mostly to the mitochondrial activity of B-CLL cells, and insufficient antioxidant defences. [32,33]. The decreased antioxidant capacity found in the sera of our B-CLL patients may be related to a consumption of antioxidants and/or to a reduced efficacy of antioxidant defences due to the systemic excess of ROS that is common in cancer [34].Accumulating evidence by two important studies suggested that increased OS and the relative deficiency of the antioxidant defence system are involved in crucial steps of B-CLL development [28,35].…”
Section: Discussionmentioning
confidence: 95%